Ensuring Quality and Safety in Chicken Slaughterhouse Practices through Microbiological Evaluation: Memastikan Kualitas dan Keamanan dalam Praktik Rumah Potong Ayam melalui Evaluasi Mikrobiologi - Sabela, Eka; Azara, Rima; Oktarina, Pramitha Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the microbiological quality of chicken meat produced at a slaughterhouse, focusing on total plate count (TPC), Escherichia coli, Coliform, Staphylococcus aureus, and Salmonella sp. In the food industry, the slaughter of animals necessitates adherence to strict technical and hygienic standards to ensure product quality and safety. A knowledge gap exists regarding the correlation between slaughterhouse practices and microbial contamination levels in meat products. The aim of this research is to assess the microbial concentration in chicken meat and evaluate the effectiveness of sanitation procedures implemented during production. Through microbiological testing conducted at the slaughterhouse laboratory, it was found that the microbial concentrations in the sampled chicken meat were within acceptable limits according to national regulations. These results underscore the importance of stringent cleanliness and sanitation protocols in slaughterhouse operations to ensure the production of high-quality and safe meat products. Highlights: Quality Control: Ensures adherence to standards for safe food production. Sanitation Priority: Strict cleanliness maintains product quality. Microbiological Testing: Results within acceptable limits assure good product quality. Keywords: Broiler Chicken, Product Quality, Microbiological Test